Experimental investigation of two-phase slug flow splitting at a micro impacting T-junction. (February 2015) - Chen, Jinfang; Wang, Shuangfeng; Zhang, Xinqiang; Ke, Hongfeng; Li, Xuanyou
Abstract: As a fluid distribution unit, the micro T-junction is commonly found in various devices, such as micro-reactors and compact heat exchangers. It is well known that phase split occurs during gas–liquid two-phase flow through T-junction and causes different qualities between the branches of the tee, which can have a significant influence on the performance of equipments downstream. This paper presented the results of an experimental investigation conducted on phase split of slug flow through a horizontal T-junction with a square cross section (500 μm × 500 μm). Nitrogen and water at room temperature of 18 °C were used as the test fluids. The inlet superficial velocity ranges of gas and liquid were 0.36–2.4 m/s and 0.1–0.9 m/s, respectively. The aqueous solutions of sodium dodecyl sulfate (SDS) with different mass concentrations were used to study the effect of surface tension. Experimental results showed that, decreasing the channel diameter drastically intensified the phase maldistribution due to the effect of surface tension. In particular, for the micro impacting T-junction, once the liquid taken off from either branch was smaller than 35%, there was no gas taken off. Besides, the effect of surface tension took on distinct characteristics under different inlet flow conditions. Specifically, for the short gas slugs, the phase maldistribution reduced with decreasing surface tension. However, for the long gas slugs, the phase maldistribution got worse with the decrease of surface tension. Finally, a correlation capable of predicting the phase split of slug flow in micro impacting T-junctions was developed.